On certain subshifts and their associated monoids - Hamachi, Toshihiro; Krieger, Wolfgang (Ergodic theory and dynamical systems, 2016)
Within a subclass of monoids (with zero) a structural characterization is given of those that are associated to topologically transitive subshifts with Property (A).
Published online: 16 September 2014
Gesehen am 15.06.2018